Évaluation des pratiques psychoéducatives et résilience : influences des ressources psychosociales et du climat social scolaire - Christiam Talavera; Guylaine Molina; Jeanne Mallet (Éducation et Socialisation)
The research on resilience has focused mainly on psycho educational intervention on risk factors in children. Studying not only "natural resilience" but how "assisted resilience" helps children deal with trauma. This change of strategy suggests that promoting practices of resilience may be a means of developing psychological skills of resilience in children. In that respect, the schools’ social environment can be used as a space of interaction to promote the emergence of social, emotional, cognitive, and volitive skills in the students. The central question of this study is how schools can include practices that foster the development of resilience skills in children? To answer this question, we used a sample of 109 high-risk children attending disadvantaged Peruvian schools. Our methodology takes into account the teachers’ and students’ perceptions of the school’s social climate, in particular (1) the relationship among students, among teachers, and between students and teachers, (2) the school organization and (3) the development of extracurricular activities. The study also includes the students’ thoughts about their psychosocial needs. The analysis of these elements provides a basis to suggest the psycho educational practices of resilience at school and teachers training.